Existence and Uniqueness Theorems for Impulsive Fractional Differential Equations with the Two-Point and Integral Boundary Conditions. (20th March 2014) - Mardanov, M. J.; Mahmudov, N. I.; Sharifov, Y. A.
Abstract : We study a boundary value problem for the system of nonlinear impulsive fractional differential equations of order α    0 < α ≤ 1 involving the two-point and integral boundary conditions. Some new results on existence and uniqueness of a solution are established by using fixed point theorems. Some illustrative examples are also presented. We extend previous results even in the integer case α = 1 .